Leucothoid amphipod and terebellid polychaete symbiosis with description of a new species of the genus Leucothoe Leach, 1814 (Crustacea: Amphipoda: Leucothoidae). Issue 1 (31st December 2022) - Kodama, Masafumi; White, Kristine N.; Hosoki, Takuya K.; Yoshida, Ryuta
Abstract : The order Amphipoda is one of the largest orders in the Crustacea, many species of which are involved in symbiotic relations with other animals. Despite the considerable diversity of the Amphipoda both in number of species and ecology, polychaete-commensalism has been poorly known and described from few species. In particular, there has been little discussion of the evolutionary origins of polychaete-commensalism relationships. Amphipods in the family Leucothoidae are known as commensal inhabitants of filter-feeding invertebrates, where they utilize the feeding current produced by their hosts. Leucothoids are typically found from three types of filter-feeding hosts: sponges, ascidians, and bivalve molluscs. Relatively little is known about leucothoids that associate with other types of hosts. An undescribed species of the genus Leucothoe associated with burrows of terebellid polychaetes from Japan has been found. We herein describe this species as Leucothoe vermicola sp. nov., providing COI mtDNA and 18S rDNA sequences for DNA barcoding. This is the first record of a symbiotic association between Leucothoidae and Terebellidae. We also provide a hypothesis of the phylogenetic position of L. vermicola sp. nov. and evolution of the polychaete-commensalism in this species. The polychaete-commensalism in the present new species may have resulted from the entry of generalist species into polychaete hosts, rather than from host-conversion from a specialist species. http://zoobank.org/urn:lsid:zoobank.org:pub:4EBA42DD-EC19-4278-B712-8BEFBC519F8F